Las deudas de tributos y sus efectos en la liquidez de la municipalidad distrital de Paijan, periodo 2010-2011 - Oliver Campos, Nathalie Blanca Leonor (2011)
In the investigation to first determine the impact of tax debts occurto Local Governments, and secondly to investigate what are the effects on the liquidity of the District Municipality of Paiján. Municipalities spend a great problem is the lack of economic resources for the execution of Works, Public Cleaning, Ornato and Payment Staff etc. This problem does not lie outside the District Municipality of Paiján, afflicting the poor contribution of FONCOMUN and especially not made payment of municipal taxes from the population thus creating evasion and arrears, as a result of this lack tax of conscious ness on the part of tax payers. Municipal Tax Administration is subject to in action on tax, adding the lack of creativity among the staff of the tax administration office and somehow the lack of specific licies by the authorities. In the District Municipality of Paiján is a lack of fiscal policy as the causes for these problems are mainly duet o lack of training and interest of managers to solve this lack of tax revenue. Little or nothing has been done in the registration of taxpayers and the cadastral survey and / or tax audit o expand its tax base. It is important to mention that it has a municipal organization that believes in its organizational structure an Office of Tax Administration performs its functions but not due to non-implementation of municipal policy documents (ROF, MOF), which are important forall governmental entity.